Bilateral differences in muscle fascicle architecture are not related to the preferred leg in jumping athletes - Aeles, J.; Lenchant, S.; Vanlommel, L.; Vanwanseele, B. (European Journal of Applied Physiology, 2017)
Purpose: In many sports, athletes have a preferred leg for sport-specific tasks, such as jumping, which leads to strength differences between both legs, yet the underlying changes in force-generating mechanical properties of the muscle remain unknown. The purpose of this study was to investigate whether the muscle architecture of the medial gastrocnemius (MG) is different between both legs in well-trained jumping athletes and untrained individuals. In addition, we investigated the effect of two ankle joint positions on ultrasound muscle architecture measurements. Methods: Muscle architecture of both legs was measured in 16 athletes and 11 untrained individuals at two ankle joint angles: one with the ankle joint in a tendon slack length (TSL) angle and one in a 90° angle. Results: Fascicle lengths and pennation angles at TSL were not different between the preferred and non-preferred legs in either group. The comparison between groups showed no difference in fascicle length, but greater pennation angles were found in the athletes (21.7° ± 0.5°) compared to the untrained individuals (19.8° ± 0.6°). Analyses of the muscle architecture at a 90° angle yielded different results, mainly in the comparison between groups. Conclusion: These results provide only partial support for the notion of training-induced changes in muscle architecture as only differences in pennation angles were found between athletes and untrained individuals. Furthermore, our results provide support to the recommendation to take into account the tension-length relationship and to measure muscle architecture at individually determined tendon slack joint angles.